Jasmonic acid alleviates cadmium toxicity in Arabidopsis via suppression of cadmium uptake and translocation. Issue 2 (2nd May 2019) - Lei, Gui Jie; Sun, Li; Sun, Ying; Zhu, Xiao Fang; Li, Gui Xin; Zheng, Shao Jian
Abstract: Jasmonic acid (JA) is thought to be involved in plant responses to cadmium (Cd) stress, but the underlying molecular mechanisms are poorly understood. Here, we show that Cd treatment rapidly induces the expression of genes promoting endogenous JA synthesis, and subsequently increases the JA concentration in Arabidopsis roots. Furthermore, exogenous methyl jasmonate (MeJA) alleviates Cd‐generated chlorosis of new leaves by decreasing the Cd concentration in root cell sap and shoot, and decreasing the expression of the AtIRT1, AtHMA2 and AtHMA4 genes promoting Cd uptake and long‐distance translocation, respectively. In contrast, mutation of a key JA synthesis gene, AtAOS, greatly enhances the expression of AtIRT1, AtHMA2 and AtHMA4, increases Cd concentration in both roots and shoots, and confers increased sensitivity to Cd. Exogenous MeJA recovers the enhanced Cd‐sensitivity of the ataos mutant, but not of atcoi1, a JA receptor mutant. In addition, exogenous MeJA reduces NO levels in Cd‐stressed Arabidopsis root tips. Taken together, our results suggest that Cd‐induced JA acts via the JA signaling pathway and its effects on NO levels to positively restrict Cd accumulation and alleviates Cd toxicity in Arabidopsis via suppression of the expression of genes promoting Cd uptake and long‐distance translocation. Abstract : Cd‐induced JA accumulation acts via JA signaling pathway and the effects of JA on NO levels to positively restrict Cd accumulation and alleviates Cd toxicity in Arabidopsis via suppression of the expression of genes, AtIRT1, AtHMA2 and AtHMA4, promoting Cd uptake and long‐distance translocation.